System simulation of mixed-signal multi-domain microsystems with piecewise linear models. - Levitan, S.P (IEEE Transactions on computer-aided design of integrated circuits and systems)
We present a component-based multi-level mixed-signal design and simulation environment for microsystems spanning the domains of electronics, mechanics, and optics. The environment provides a solution to the problem of accurate modeling and simulation of multi-domain devices at the system level. This is achieved by partitioning the system into components that are modeled by analytic expressions. These expressions are reduced via linearization into regions of operation for each element of the component and solved with modified nodal analysis in the frequency domain, which guarantees convergence. Feedback among components is managed by a discrete event simulator sending composite signals between components. For electrical, and mechanical components, interaction is via physical connectivity while optical signals are modeled using complex scalar wavefronts, providing the accuracy necessary to model micro-optical components. Simulation speed vs. simulation accuracy can be tuned by controlling the granularity of the regions of operation of the devices, sample density of the optical wavefronts, or the time steps of the discrete event simulator. The methodology is specifically optimized for loosely coupled systems of complex components such as are found in multi-domain microsystems.